The faculty trust and the school climate among the stakeholders at Saint Jude Catholic School - Mei, Li (Animo Repository, 2013)
This study aimed at exploring the statistically significant relationship between the level of the faculty trust in principal, colleagues (co-teachers), parents, and student, and the school climate in terms of principal, teachers, parents, and students behavior as perceived by the randomly selected teachers at Saint Jude Catholic School (SJCS) in Metro Manila. To achieve this aim, a quantitative descriptive-correlation study was conducted. In order to investigate the correlation study, Faculty Trust Survey (or Omnibus T-Scale) (Tschannen-Moran & Hoy 2003), Organizational Climate Description Questionnaire for Secondary schools (OCDQ-RS) (Hoy, et al., (1991), Parental Involvement Questionnaire (Ho, 2007), and NASSP School Climate Survey (Olive, 2005) were randomly administered to 113 teachers at SJCS. To support the correlation study, a semi-structured and open-ended in-depth one-on-one interview was conducted to 30 teachers at SJCS. The results revealed that in general the level of the faculty trust in principal, colleagues (co-teachers), parents, and students is positively related to the school climate in terms of principal, colleagues, parents, and students behavior. Peculiarly, the level of faculty trust in principal, teachers, parents, and students is positively related to principal supportive, teacher engaged, intimate, parental involvement, parental involvement in terms of parenting, communicating, and community collaboration, teacher-student relationships, the student academic orientation, the student behavioral values in self-discipline and tolerance, and the student-peer relationships behavior respectively. However, the level of faculty trust in principal is negatively related to principal directive behavior. Based on the general findings of this study, recommendations for future investigations are forwarded.